2009
DOI: 10.1002/cncr.24165
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pregnancy on breast cancer outcomes in women ≤35 years

Abstract: BACKGROUND:Some evidence suggests that women with pregnancy‐associated breast cancers (PABC) have a worse outcome compared with historical controls. However, young age is a worse prognostic factor independently, and women with PABC tend to be young. The purpose of the current study was to compare locoregional recurrence (LRR), distant metastases (DM), and overall survival (OS) in young patients with PABC and non‐PABC.METHODS:Data for 668 breast cancers in 652 patients aged ≤35 years were retrospectively review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
111
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 16 publications
13
111
3
4
Order By: Relevance
“…As far as outcome of PABC is concerned data are conflicting: some authors showed no difference in outcome of PABC and non-PABC cases [14,16,24], while others consider PABC as having unfavorable prognosis [1,[7][8][9]. In a recent metaanalysis of 30 studies, Azim et al found that PABC patients had poor overall survival especially if breast cancer was diagnosed within 1 year postpartum [25].…”
Section: Discussionmentioning
confidence: 99%
“…As far as outcome of PABC is concerned data are conflicting: some authors showed no difference in outcome of PABC and non-PABC cases [14,16,24], while others consider PABC as having unfavorable prognosis [1,[7][8][9]. In a recent metaanalysis of 30 studies, Azim et al found that PABC patients had poor overall survival especially if breast cancer was diagnosed within 1 year postpartum [25].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in two studies included in the integrative review, the results did not show statistically significant difference concerning survival rate in a comparison between PABC women and the control group (nonpregnant women) (17)(18) .…”
Section: Discussionmentioning
confidence: 73%
“…Beadle et al (18) To compare the rates of locoregional recurrence, metastases and survival in young patients (35 years old or younger) who developed PABC to non-PABC women.…”
Section: Study Objective Results Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the desire of these women to be pregnant may delay the diagnosis, many breast cancers becoming clinically evident during gestation or immediately after delivery [18][19][20]. Hence, breast palpation, ultrasonography of breasts and armpits, and biopsy of the tumor tissue (punch biopsy) are considered to be the gold standard in the evaluation of masses occurring in a woman under 30 [14].…”
Section: Discussionmentioning
confidence: 99%